1997
DOI: 10.1111/j.1540-5915.1997.tb01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Factors and Intuition‐based Methods for Facility Network Design

Abstract: Logistics managers frequently utilize decision support systems @SS) to make facility network design decisions. Many DSS do not provide optimization capabilities, but instead rely on scenario evaluation as a means for developing solutions. We experimentally assessed the performances of decision makers, including experienced managers, who used four variants of a scenario evaluation-based DSS to solve realistically sized network design problems of varying complexities. Complexity factors included DSS attributes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Sengupta and Abdel-Hamid (1993) examine this question in the context of a set of simulated software development Product development Chow and Haddad (1991), Silver (1990) Basadur et al (1986), Chow and Haddad (1991), Garland (1990), Garland et al (1990), Schmidt et al (2001), Sengupta and Abdel-Hamid (1993), Whyte (1991) Connolly and Dean (1997), Sengupta and Abdel-Hamid (1993) Inventory and DC management Kernan and Lord (1990), Schweitzer and Cachon (2000) Kernan and Lord (1990), Moxnes (1998), Robinson and Swink (1995), Smelcer and Carmel (1997), Swink (1995), Swink and Robinson (1997), Swink and Speier (1999) Kernan and Lord (1990), Swink (1995), Swink and Robinson (1997), Schweitzer and Cachon (2000) Quality management and control Gully et al (2002), Soman and Shi (2003) Ghosh and Ray (1997), Larson and Callahan (1990), Pei and Reneau (1990), Robinson and Robinson (1994), Stanton and Barnes-Farrell (1996) Larson and Callahan (1990), Stanton and Barnes-Farrell (1996) Production and workflow management Audia et al (1996), Johnson et al (2002), Stading et al (2001) Aiello and Kolb (1995), Anson et al (1995), …”
Section: Product Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Sengupta and Abdel-Hamid (1993) examine this question in the context of a set of simulated software development Product development Chow and Haddad (1991), Silver (1990) Basadur et al (1986), Chow and Haddad (1991), Garland (1990), Garland et al (1990), Schmidt et al (2001), Sengupta and Abdel-Hamid (1993), Whyte (1991) Connolly and Dean (1997), Sengupta and Abdel-Hamid (1993) Inventory and DC management Kernan and Lord (1990), Schweitzer and Cachon (2000) Kernan and Lord (1990), Moxnes (1998), Robinson and Swink (1995), Smelcer and Carmel (1997), Swink (1995), Swink and Robinson (1997), Swink and Speier (1999) Kernan and Lord (1990), Swink (1995), Swink and Robinson (1997), Schweitzer and Cachon (2000) Quality management and control Gully et al (2002), Soman and Shi (2003) Ghosh and Ray (1997), Larson and Callahan (1990), Pei and Reneau (1990), Robinson and Robinson (1994), Stanton and Barnes-Farrell (1996) Larson and Callahan (1990), Stanton and Barnes-Farrell (1996) Production and workflow management Audia et al (1996), Johnson et al (2002), Stading et al (2001) Aiello and Kolb (1995), Anson et al (1995), …”
Section: Product Developmentmentioning
confidence: 98%
“…Robinson and Swink (1995) study alternative methodologies for solving logistics problems, ranging from intuition, scenario evaluation, heuristic, and optimization procedures. Swink and Robinson (1997) examine the relative solution performance of four different scenario-based DSS, also in a logistics context. They find that having incremental cost improvement cues significantly improved performance.…”
Section: Inventory and DC Managementmentioning
confidence: 99%
“…Given the detrimental influence of task complexity on computer‐based decision making (Robinson & Swink, 1994; Crossland, Wynne, & Perkins, 1995; Swink & Robinson, 1997) and the likely negative influence of interruptions (Cellier & Eyrolle, 1992; Shiffman & Griest‐Bousquet, 1992; Schuh, 1978), an important question is whether information systems can be designed to mitigate these effects (Rouncefield, Viller, Hughes, & Rodden, 1995). Prior research has identified information presentation as a factor affecting decision performance (DeSanctis, 1984; Tan & Benbasat, 1990; Vessey, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…According to research examining pre-attentive processing, a person's reaction time to a given stimulus depends on the amount of material to be processed, even if it is presented outside the focus of attention (Schweizer, 1994;Schweizer, 1995). Multiple studies investigating the relationship between task complexity and various decision-making performance measures have found performance to degrade as complexity increases (e.g., Byström and Järvelin, 1995;Crossland et al, 1995;Mennecke et al, 2000;Swink and Robinson, 1997). Similar to the effects of time pressure, increased task complexity demands increase cognitive effort, and users reach for satisficing strategies in decision-making in an attempt to decrease effort (e.g., Paquette and Kida, 1988).…”
Section: Task Complexitymentioning
confidence: 99%